Proceedings of the Second International Conference on Computational Intelligence and Informatics ICCII 2017 - Bhateja, Vikrant; Tavares, João Manuel R.S.; Rani, B. Padmaja; Prasad, V. Kamakshi; Raju, K. Srujan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
The volume contains 69 high quality papers presented at International Conference on Computational Intelligence and Informatics (ICCII 2017). The conference was held during 25-27, September, 2017 at Department of Computer Science and Engineering, JNTUHCEH, Hyderabad, Telangana, India. This volume contains papers mainly focused on data mining, wireless sensor networks, parallel computing, image processing, network security, MANETS, natural language processing, and internet of things.
Preface -- About the Editors -- Organizing Committee -- Table of Contents -- 69 papers -- Author Index.
Keywords: Computational intelligence; Telecommunication; Bioinformatics; Computational Intelligence; Communications Engineering, Networks; Computational and Systems Biology